Evaluación de los daños causados por el virus dorado del frijol (VMDF) - Menten, J.O.M; Neto, A.T; Ando, A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Quantitative evaluation of losses caused by golden mosaic virus in beans (BGMV) is very difficult under field conditions due to the difficulty in having plots completely free of the disease for comparison with infected plots. Research was carried out at Piracicaba, Sao Paulo State, Brazil, in a field used for seed multiplication of Carioca 6C, line during the 1978 dry season, where incidence of the BGMV was not uniformily observed. Four 50 meter length rows were chosen at random during flowering and apparently healthy plants and plants showing typical symptoms were tagged. After harvesting, production and seed characterictics were assessed. Results showed that productivity of infected plants had been reduced 64% in grain for comsumption and by 71% in seed for multiplication as compared to healthy plants. Reduction in weight of 100 seeds, germination, emergence, first counting of germination test, rate of emergence, hypocotyl length, seedling height and seed health were respectively 36.8, 4.8, 5.3, 9.5, 7.4, 13.0, 17.4 and 63.6%. Grain for comsumption from infected plants showed a pronounced deterioration in quality, especially in colour and format, which would cause a marked reduction in their commercial value.